Acute interstitial nephritis secondary to vedolizumab. Issue 11 (19th November 2021) - Simpson, Nicholas; Seenan, John Paul; Patel, Rajan; Kipgen, David
Abstract : We present a patient with an acute kidney injury thought secondary to acute interstitial nephritis as a result of vedolizumab maintenance therapy for Crohn's disease. This appears to be a rare but serious side effect in patients receiving this treatment which clinicians should consider in the event of renal dysfunction.